Mental health intervention strategies in the COVID-19 pandemic: systematic review (Research, Society and Development, 2022)
Goals: The aim of this study was to conduct a systematic review of clinical trials dealing with mental health interventions in the COVID-19 scenario. Methods: The research of scientific papers was carried out by two independent researchers, including papers published until March 2021, as a full text in Portuguese or in English. The clinical trials used in the systematic review were obtained from the Pubmed and Scielo electronic databases. Results:  Through the analysis of the works included in the review, which addressed: philosophy intervention and mindfulness-based intervention in elementary school children; online multimedia psychoeducational intervention and integrated internet-based intervention in adult patients hospitalized with COVID-19; Intervention through the Awareness, Courage and Love (ACL) protocol in couples and intervention based on videos of forest environments in adults, the result was that online interventions can also be effective in improving mental health in the context of the pandemic of COVID-19. Although the analyzed studies addressed different audiences, in all of them the results of the intervention were positive in relation to what had been proposed. Conclusion: There are interventions performed in mental health in the context of COVID-19 that have high scientific evidence, being easy to perform and low cost. Therefore, public policies focused on the mental health of the population should be elaborated based on the available scientific evidence, aiming to reduce mental disorders arising or accentuated by the current scenario of the SARS-CoV-2 pandemic.